Atmospheric corrosion of carbon steel: Results of one-year exposure in an andean tropical atmosphere in Colombia - Ana C. Santa; Diego A. Montoya; Jose A. Tamayo; Maryory A. Gómez; Juan G. Castaño; Libia M. Baena (Heliyon, 2024)
In this study was examined the response of carbon steel to atmospheric corrosion after one-year exposure in Valle de Aburrá, a subregion located in northwestern Colombia. The study involved the assessment of material mass loss and corrosion rate, the characterization of atmospheric aggressiveness, and the analysis of the morphology and composition of corrosion products in five different sites. Climatological and meteorological factors were assessed by testing for chloride content, sulfur dioxide levels, and time of wetness (TOW). The analysis of corrosion products was conducted using scanning electron microscopy (SEM), X-ray diffraction (XRD), and Raman spectroscopy. Based on corrosion rates, two sites exhibited a more aggressive environment, with a corrosivity category of C3, while the remaining sites were categorized as C2. The study confirmed the presence of lepidocrocite and goethite phases on the surface of carbon steel at all test sites. Data analysis revealed that both the TOW and the industrial activity significantly influence the corrosion of this metal.